Utilizing e-comic media for differentiated learning: A Realistic Mathematics Education approach to stimulate learning interest - Fitriani, Nelly; Leton, Samuel Igo (Universitas Papua, 2024)
The primary aim of this study is to ascertain the learning preferences of junior high school students and evaluate their interest in mathematics following instruction utilizing e-comic media grounded in realistic mathematics education within a framework of differentiated learning. Employing a mixed methods approach with an exploratory sequential design, the study targets junior high school students in the West Bandung region, with a cohort of 30 eighth-grade students selected as the sample. Questionnaires serve as the primary instruments to discern students' learning styles. Qualitative analysis involves scrutinizing these styles vis-à-vis their learning requisites. The ensuing analysis informs the customization of instructional media tailored to students' preferences, subsequently validated by experts. The study culminates in administering interest assessment questionnaires post-instruction. Findings and data analysis reveal three predominant learning tendencies among students: visual (37%), auditory (20%), and kinesthetic dominated (43%). The developed instructional media, validated and tested for efficacy, effectively caters to these learning styles. Application of this media demonstrates heightened interest in learning mathematics compared to traditional instructional methods.